140k views
2 votes
Find the value of f(–3) and g(3) if f(x) = –6x + 3 and g(x) = 3x + 21x^–3.

f(–3) = 21 g(3) = 9.78
f(–3) = –18 g(3) = –9.78
f(–3) = –3 g(3) = 30.04
f(–3) = 15 g(3) = 8.22

2 Answers

4 votes

Answer:

f(-3)=21

Explanation:

Plug in -3 for x. -6•-3=18. 18+3=21.

User Thays
by
5.3k points
4 votes

Answer:

f(–3) = 21 g(3) = 9.78

Explanation:

Given functions,


f(x) = -6x + 3-----(1)


g(x)=3x+21x^(-3)-----(2)

Put x = -3 in equation (1),


f(3) = -6(-3) + 3 = 18 + 3 = 21

Put x = 3 in equation (2),


g(3) = 3(3) + 21 (3)^(-3)=9 + (21)/(3^3)=9+(21)/(27)=9.777778\approx 9.78

Hence, first option is correct.

User Akhilesh Kamate
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.